Um estudo sobre a influência de fenômenos metereológicos extratropicais na variação do clima do nordeste - Buchmann, Julio (Universidade Federal do Rio de Janeiro, 1981)
Study the drought and rain anomalies in the Northeast of Brazil. This can be caused by the variations in the synoptic pressure systems located in the middle and high latitudes of the Northern Hemisphere, mechanism of lateral forcing. To achieve this is a diagnostic study was undertaken to colletate these anomalies with the fluxes of momentum and potential energy and the wind field. A physical mathematical model was then formulated using appropriate boundary conditions in arder to simulate and to understand how the anomalies are set in the equatorial region, and verified against the diagnostic studies. The diagnostic studies show that for the month of dy (.rainy) years the flow deviation-from the trade winds compared with the normal wind field are relatively weak (intense) in the direction of the Semi-Arid Northeast Brazil. This agrees well with Namias results that the synoptic high pressure systems located in the South Atlantic Ocean in the rainy, (dry) months are, found more (less) to the south of the Northeast coast, also in agreement with the results of Hastenrath and Heller. With respect to the quantities |v 'ϕ' |e |u ' v '| their values and correspondent curves agree with the results of Mak. These results caracterize the critical latitude and show that a great part of the momentum flux from the equatorial region of South America towards the Northern Hemisphere originates in a equatorial region between 50°W e 20ºW. A two layer primitive equation rnodel was used in simulated study to understand the coupling mechanism. The boundary condition in the north hemisphere is of the type a basic state plus stationary perturbation (the greater amplitude component was found frorn the Fourier analysis of the parameters deviation u e v with respect to the normal wind field). A solution, confined in the equatorial region was obtained after 5-6 days of integration, in accordance with Mak. This shows a probable interaction between the middle latitude flows and the tropics (at least in non-linear finite difference model).In ...